Exploring the Interactions on an Online Narrative Writing Platform - Nagaletchimee Annamalai; Tan Kok Eng; Amelia Abdullah; Sorojini Sivagurunathan (UUM Press, 2015)
Purpose - This paper reports a study that investigated the interactions of six students learning to write narrative essays on an online narrative writing platform (ONWP). Participants were six students and a teacher from an urban Chinese Secondary School in the northern region of Malaysia.   Methodology -The qualitative data used in this study were online interaction archives and narrative essays collected from an ONWP used by the teacher to teach narrative writing. The student-teacher interactions were coded based on the categories related to cognitive, teaching and social presences as suggested by the Community of Inquiry Model (Garrison, Archer & Anderson, 2000).   Findings - Findings indicated that the cognitive, teaching and social presences suggested by the CoI model were present in the interactions while students were engaged in the ONWP. However, certain descriptors of the CoI were not found in the study. The major contribution of this study is the single, dual and triple phases which emerged from this study. The essays' scores revealed that the students improved in their narrative writing ability after engaging in the ONWP.   Significance - The fi ndings have placed the model in a new environment involving the application of CoI model in a Chinese Secondary School. Being online to fulfil wide-ranging tasks does not only involve critical thinking but also creative writing. Teachers involved in online teaching and learning activities need to encourage students to be involved in critical thinking. Students should also realise that there is more to learn in writing than just making corrections based on the comments.